2015
DOI: 10.1111/pbr.12257
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal regions associated with thein vitroculture response of wheat (Triticum aestivumL.) microspores

Abstract: Generation of doubled haploid plants is a powerful tool in breeding, as homozygous individuals will be obtained directly from hybrids. However, genotype variability in regeneration efficiency of most European wheat (Triticum aestivum L.) varieties has limited its use in wheat. This study intended to identify quantitative trait loci (QTLs) for green plantlet regeneration from wheat microspore cultures. A QTL analysis using DArT markers was conducted based on a bi-parental F 3 population, derived from a cross be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
(77 reference statements)
2
21
0
1
Order By: Relevance
“…Additionally, variation in the inheritance patterns between the populations indicates the presence of different numbers of distinct alleles in their paircross parents (Madsen et al 1995;Torp et al 2001;Nielsen et al 2015). For example, non-androgenic parent P133 may harbour superior alleles for microspore embryogenesis and plant regeneration compared to P10.…”
Section: Genetic Control Of Androgenic Capacitymentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, variation in the inheritance patterns between the populations indicates the presence of different numbers of distinct alleles in their paircross parents (Madsen et al 1995;Torp et al 2001;Nielsen et al 2015). For example, non-androgenic parent P133 may harbour superior alleles for microspore embryogenesis and plant regeneration compared to P10.…”
Section: Genetic Control Of Androgenic Capacitymentioning
confidence: 99%
“…Additionally, the absence of a correlation between QTL explaining variation in green plant production with embryo formation or plant regeneration was reported in wheat (Torp et al 2001;Nielsen et al 2015). Several other possibilities may be considered instead; for example, dominant control of green plant production by several genes, alleles for which are contributed solely by the androgenic parents (Tuvesson et al 1989;Opsahl-Ferstad et al 1994b), or complementation of recessive beneficial alleles present in a heterozygous state within the non-androgenic parents (Madsen et al 1995).…”
Section: Genetic Control Of Androgenic Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…The other methods for DH plant production are AC and isolated microspore culture. AC is frequently used in breeding and applied research of common wheat (Lantos et al, 2013;Castillo et al, 2015, Nielsen et al, 2015, while published reports of in vitro androgenesis induction are limited in spelt wheat. Takács et al (1994) reported on the androgenesis induction in AC of a spelt wheat genotype, in which the number of responsive anthers was 6.4%.…”
Section: Introductionmentioning
confidence: 99%